O ensino do esporte orientação na escola: possibilidades e limites de uma proposta à luz da metodologia crítico-superadora - Cauper, Dayse Alisson Camara (2018)
The research presented here aims to study the teaching of orienteering sports in high school physical education classes. The research problem consists in identifying the possibilities and the limits for the teaching of this corporal practice of adventure in the School Physical Education in the light of the critical-overcoming methodology. The general objective is to develop a didactic-pedagogical sequence for the teaching of orienteering, which contributes to the expansion of the knowledge and learning possibilities of the high school students of the Center for Education and Research Applied to Education of the Federal University of Goiás (CEPAE / UFG). The research is based on historical-critical, historical-cultural and critical-overcoming theories, especially regarding the triad content-form-recipient (MARTINS, 2016a). It is a participant research that uses the following data collection instruments: questionnaires, field diary and interview. The research was finalized with the elective discipline Corporal practices of adventure - orienteering sport, when the didactic-pedagogical sequence was materialized with the students of the last stage of basic education. The data, also analyzed from the content-recipient-triad, indicate not only that it is possible but also to enrich the symbolic universe of the students through the teaching of classical knowledge in Physical Education. However, they point to some limits, among which are: the lack of didactic material on content, the complexity of theoretical references (critical-overcoming methodology, historical-critical pedagogy and historical-cultural psychology), as well as students' . Although limits have been identified in the course of this teaching process, it should be emphasized that pedagogical action occurred in the spaces of contradiction, seeking to overcome them dialectically and to present feasible alternatives for the educational work in secondary education.